Do Sustainability Disclosures Matter? An Empirical Analysis of Banks’ Financial Performance in Indonesia and Malaysia - Rusli, Moch.; Wati, Asiah; Habibie, Haq Muhammad Hamka (MALIA: Journal of Islamic Banking and Finance, 2025)
This study aims to investigate the impact of sustainability reporting, as measured by the ESG score, on the financial performance of banks in Indonesia and Malaysia, specifically focusing on Return on Assets (ROA) and Return on Equity (ROE). Additionally, macroeconomic variables, including inflation (INF), GDP growth, unemployment rate (UNP), and bank-specific factors such as Net Profit Margin (NPM) and Debt to Equity Ratio (DER) are considered. Using panel data from 2020 to 2024, the study applies the Random Effects Model (REM) to analyze the relationships between these variables. The results indicate that ESG disclosure does not have a significant on the financial performance of banks in both countries. However, NPM significantly positively both ROA and ROE. Macroeconomic variables show mixed results, with inflation having a positive impact on financial performance, GDP negatively affecting ROE, and UNP having a positive effect on ROE but no significant effect on ROA. The study suggests that macroeconomic stability plays a more substantial role in shaping bank performance compared to sustainability disclosure, particularly in emerging markets like Indonesia and Malaysia. Further research could explore the long-term effects of sustainability reporting and consider crisis periods to better understand the dynamics between sustainability and financial performance in the banking sector.